Daily cardiac autonomic responses during the Tour de France in a male professional cyclist - Bourdillon, Nicolas; Bellenoue, Samuel; Schmitt, Laurent; Millet, Grégoire P. (Frontiers in Neuroscience, 2024)
Background -Heart rate variability (HRV) is a common means of monitoring responses to training, yet in professional cycling one may question its usefulness, particularly during multiday competitions as Grand Tours.Objectives -Report and analyse HRV responses in a male professional cyclist over a season, including the Tour de France.Methods -A professional cyclist recorded resting and exercise inter-beat-intervals during five months, comprising a training period with two altitude sojourns and two competition blocks, including the Tour de France. Resting recordings lasted five minutes in the supine position and were used for computation of mean heart rate (HR), root mean square of the successive differences (RMSSD), power in the low-and high-frequency bands (LF and HF, respectively). Training load quantification was based on recorded HR during exercise and expressed as Training Impulses (TRIMPS).Results -LF (3319±2819 vs. 1097±1657 ms 2 ), HF (3590±1858 vs. 1267±1683 ms 2 ) and RMSSD (96±26 vs. 46±30 ms) were higher and HR (47±4 vs. 54±2 bpm) lower during the training period, when compared to the two competition blocks. The coefficient of variation (CV) was significantly lower during the training period than during the two competition blocks for RMSSD (26 vs. 72%), LF (85 vs. 160%) and HF (58 vs. 141%).Discussion -The present study confirms that monitoring daily HRV responses during the training periods is valuable in professional cycling; but questions its usefulness during the Tour de France. Moreover, previous suggestion that CV in RMSSD would help to predict poor performance was not confirmed in a professional cyclist.